Implementasi Strategi Ekspositori dalam Pembelajaran Sejarah Kebudayaan Islam di Madrasah Aliyah - Nisa, Yuni Khairun; Wahyudin, Wahyudin; Sari, Nia Novita; Muniro, Dina Dhiya’an; Pratama, Krisna Ananda (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2025)
Technological advancements have indeed facilitated the learning process, but their utilization is not evenly distributed across Indonesia due to economic constraints and internet access in various regions. This situation presents a challenge for SKI teachers to ensure optimal learning despite limited digital resources. This study aims to analyze how expository learning strategies can be used as an effective alternative to improve student understanding without relying on technology. The study was conducted using a descriptive qualitative method with a narrative literature review approach, which examined various references from Google Scholar relevant to the topic. The study's results indicate that the expository strategy can be implemented efficiently because teachers can deliver material in a structured manner, utilize simple media, and strengthen student understanding through lectures, direct explanations, and question-and-answer interactions. The study's conclusions confirm that the expository strategy is an appropriate choice for Islamic Religious Education (SKI) learning in areas with limited access to technology. This research provides theoretical contributions by strengthening references to non-digital learning in Islamic religious education, as well as practical contributions by recommending methods for teachers and educational institutions to maintain the quality of learning in low-technology environments.